PERAN ASPEK SOSIAL BUDAYA DALAM PENGEMBANGAN PERMUKIMAN PERKOTAAN PADA KAWASAN PERMUKIMAN BERLATAR BELAKANG SEJARAH DAN PERTUMBUHAN KOTA (The Role of Social and Cultural Aspects on Urban Settlement Development in Historical and Urban Growth Based Setlleme - Firmansyah Bachtiar (Tesa Arsitektur, 2015)
The increasing growth of urban settlements often creates uncontrolled dispersion of slum area. As an approach to upgrade the slums, Central Government of Indonesia has launched Community Life Improvement Program for the Urban Poor which focussed on physical stimulants programs for slums and housing infrastructure development. Within the development process, the stimulants given were often misplaced and not fully accepted by the community because of the lack of public participation and the ignorance of social and cultural context. This research aims to identify the role of the social and cultural aspect that plays an important role on urban settlement development. It focuses on the identification of social cultural aspects on two locations (Tallo, Makassar, and Tamansari, Bandung) which have two different backgrounds based on its historical growth. This research based on qualitative approach and uses questionnaire, interview and field observation as data collecting instruments. The data will be compared based on the difference of community perception and value regarding to the actual development and social cultural aspects. The result will be formulated as determinant factors that need to be considered in developing urban settlement based on local social and cultural context